"Bureaucratic society" process - Vaičiulis , Marijus (Lietuvos matematikos rinkinys, 1998)
In this paper a zero range process with memory is discussed. It is a "bureaucratic society" process. It is just alike the zero range process. A theorem of invariant measures is proved, hydrodynamics limit is analysed.